(untitled) (قضايا سياسية, 2023)
The security of any country cannot be achieved by simply securing its territory. The era of globalization, regionalism, rapid transfers, and interdependence along with the political transformations experienced by the Arab world and the region have all contributed to the emergence of a fragile security environment on the Iraqi border that affected Iraq’s national security. Those direct and indirect threats near Iraq’s borders and their impacts on Iraq’s security may affect Iraq’s relationships with the neighboring countries. As the nature and sources of threats that stem from non-state actors vary, the rise of terrorism and organized crimes and the change in the nature of security threats have impacts on Iraq’s national security.